PRODUCT CHARACTERISTICS OF TRITICUM PETROPAVLOVSKYI AND ITS SPONTANEOUS MACROMUTANTS - B. V. Romanov; K. I. Pimonov (Зерновое хозяйство России, 2019)
The studies were conducted on the experimental field of the FSBSI “Federal Russian Agricultural Research Center”, whose soils are ordinary blackearth (chernozem). 25 productive shoots of each sample were taken in their full ripeness, and, when the seeds reached standard humidity, there was performed a structural analysis in the laboratory. T. petropavlovskyi and spontaneous macromutant forms emerged from cultivation were used as the objects of study. In the process of a long-term cultivation of T. petropavlovskyi in the collection, there were identified numerous spontaneous macromutant forms of a specific nature. The paper presents the study results of the product characteristics of T.petropavlovskyi and spontaneous macromutant forms which are phenotypically close to T. spelta and soft-like T. aestivum and typical soft wheat T. aestivum. It has been established that product characteristics of speltoid macromutant wheat are significantly inferior to the original T. petropavlovskyi and macromutant soft wheat T. aestivum. Product features of soft-like macromutant T. aestivum is similar to the original T. petropavlovskyi, but has a smaller sprout weight and, correspondingly, lower grain productivity. The most promising variety for breeding process is the macromutant typical soft wheat T. aestivum, which forms a larger number of grains and, due to this, has an advantage in ‘kernel weight per head’ over all samples, including the initial form. The value of this macromutant form can also be determined by the high coefficient of specific productivity (Csp), which indicates a more efficient work of its vegetative organs. Consequently, the macromutant T. aestivum, which is phenomenally similar to the existing varieties of soft wheat, promises a high hybridization efficiency with the latter. Thus, the macromutant form of T. aestivum, developed on the basis of the T. petropavlovskyi genotype, is of some value as an initial material for breeding practice.